Effectiveness of mindfulness based stress reduction program (MBSR) on stress among nursing students- a mixed method study - Gautam, Anamika; Palanivelu, Srinivasan; Kaur, Gurvinder (International Journal Of Community Medicine And Public Health, 2020)
Background: Stress is not always avoidable but learning techniques to manage stress can develop overall wellbeing by decreasing the physical, psychological, spiritual, and social effects of stress. Learning to manage stress through holistic self-care with MBSR techniques could help to decrease the negative effects of stress. Methods: Mixed method research approach and concurrent dominant (QUAN+qual) design was selected. Total 120 nursing students was included in the study with identical sampling approach. Data was collected by using sample characteristics proforma, DASS-42 (14 items of stress) and structured open-ended questionnaire. Total 7 sessions of MBSR was administrated in the experimental group for 40 minutes. Results: Finding of the study showed that the mean score in the experimental group was lower than the comparison group (12.02 versus 21.82: t=10.12, p=0.001). The major themes emerged were stress and quality of life, body and mind. Conclusions: The study concluded quantitatively that MBSR was effective in reducing stress among nursing students and improved their daily living as well as mental health. Qualitatively the study revealed that stress influence their academic performance and personal life negatively and some student able to fight in stressful situation where as some prefer to flight by using negative defence mechanism.